Esensi Ilmu dalam Filsafat Ekono Esensi Ilmu dalam Filsafat Ekonomi Islam - Awaluddin, Murtiadi; Tawwab, M. Abdut; K, Amiruddin; Arifin, Asriadi (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
The life of the world today is controlled by two major powers, namely the economy and faith (religion). Economic life becomes the standard of living of a nation-state. Even the superiority of a country is measured based on the level of economic progress and the measure of the degree of success becomes very materialistic. Behind this, a new phenomenon has arisen showing that economic power is no longer focused on material strength alone, but seeks ways that economics can unite with ethical and spiritual forces or known as integrative business ethics and spirituality. The essence of knowledge in Islamic economic philosophy has a more substantial nature and is different from other economic views. The basis of truth believed by Islamic economics (fiqh muamalah) is based on what is described in the revelation (al-Quran and Hadith) so that the manifestation of the objectives of Islamic economics will appear as a system that saves all aspects of human life both in the frame of individual ownership rights as well as in the goal is to prosper many people